A preliminary study of normative speech rate values of Turkish speaking adults - Emrah Cangi, Mehmet; Işıldar, Ayşe; Tekin, Aleyna; Buse Saraç, Ayşe (ENT Updates, 2020)
Objectives: One of the main prosodic components of language is the rate. Speaking and articulation rates are two different measurements that reflect various aspects of each other. This study mainly aimed to present preliminary normative data related to speaking rate, reading rate, articulation rate and articulation rate in reading for Turkish-speaking adults and also aimed to compare these four measurements in terms of gender. Methods: The present study included 84 university students (42 males and 42 females) aged between 19-24 years old whose native language was Turkish. Power analysis was calculated based on the articulation rate. Speech and articulation rates were measured by taking 400-syllable conversational speech samples from each participant. A text was used from the Adult II section of the Turkish version of the Stanford Binet Intelligence Test to measure their reading rates. The speaking and reading samples obtained were recorded with a voice recorder and analyzed with the PRAAT software. Results: There was a statistically significant difference both between their speaking and reading rates, and between articulation rate and articulation rate in reading. Male participants had significantly higher articulation rates in speaking and reading than females. Conclusion: The present study provided evidence that the speech rate is low and articulation rate is high in Turkish. It concluded that the significant difference between articulation rates by gender in many languages is also valid for Turkish.